1996
DOI: 10.1007/bf02522462
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet‐activating factor receptor expression in human B cells and B cell lines

Abstract: We extended our previous data regarding the modulation of human platelet-activating factor receptor (hPAF-R) expression on human B cell lines as well as normal B cells. First, we showed that hPAF-R mRNA was present in B cell lines expressing membrane hPAF-R, but was absent from cell lines devoid of hPAF-R. Second, enhanced hPAF-R membrane expression induced in IM9 line by IL4 was preceeded by hPAF-R mRNA accumulation that was detectable by 8 h and which peaked at 24 h. Similar results were observed for 10 nM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Phorbol ester is another extensively studied regulator of PAFR. Although most studies suggest that PKC activation negatively modulates PAFR expression or its response to PAF (23,24,48,49), other reports indicate opposite effects (11,28). Some cytokines, inflammatory mediators, and hormones have also been shown to modulate PAFR in various cell types (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Phorbol ester is another extensively studied regulator of PAFR. Although most studies suggest that PKC activation negatively modulates PAFR expression or its response to PAF (23,24,48,49), other reports indicate opposite effects (11,28). Some cytokines, inflammatory mediators, and hormones have also been shown to modulate PAFR in various cell types (6).…”
Section: Discussionmentioning
confidence: 99%
“…Nguer et al (11) reported that PMA increased PAFR mRNA and surface expression in human tonsillar B cells. They also found that PDB/ION increased PAF binding to human peripheral blood B cells (10). There are several possibilities accounting for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAF is known to enhance, in vitro, the number of its own receptors on blood cell types such as monocytes and lymphocytes. 27,28 Speculating that if PAF acts during SLE it might have a similar effect, we thus investigated the presence of membrane PAF-R on circulating blood cells of SLE patients. Our results indicate that PAF-R is not detected on lymphocytes, monocytes and granulocytes of SLE patients without active nephritis.…”
Section: Discussionmentioning
confidence: 99%